GAYA KEPEMIMPINAN SEPERTI TERGAMBAR DALAM NOVEL â€œFOR WHOM THE BELL TOLLSâ€ KARYA ERNEST HEMINGWAY - BELLA, SURYA A.; WANTASEN, ISNAWATY L.; RATTU, JULTJE A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research is entitled â€œStyles of Leadership as Reflected in the Novel â€˜For Whom the Bell Tollsâ€™ by Ernest Hemingwayâ€. In this research, the writer focuses on the styles of leadership as reflected in the novel. The novel itself is based on Hemingwayâ€™s experiences during the Spanish Civil War and features an American protagonist, named Robert Jordan, who fights with Spanish guerrillas for the Republicans. The purpose of this research are to identify and classify the styles of leadership as reflected in the novel and to analyze how styles are reflected through the novel. In this research the writer used qualitative method and described it descriptively. The writer analysed the leadership styles through the character in the novel by using Martinâ€™s theory of characterisation (2004) by looking on characterâ€™s features, actions, intentions, desires, and traits. The data were analysed based on Golemanâ€™s theory styles of leadership (2000). There are six styles of leadership, those are: coercive, authoritative, affiliative, democratic, pacesetting and coaching.The results of this research shown six styles of leadership as reflected in the novel, those are coercive, authoritative, affiliative, democratic, pacesetting, and coaching. They are reflected by nine character in the novel.Keywords: Leader, Styles of Leadership, Characterisation, Ernest Hemingwayâ€™s Novel